Melhorias no Hospital das Clínicas de Ribeirão Preto – SP: reformas de adequação e implantação do Laboratório de Medicina Nuclear e PET - CT - Pajolla, Rafaela Abreu (Universidade Federal de São Carlos, 2023)
Over time the area of medicine has presented significant advances due to the development of new technologies, diagnostic equipment and treatment of diseases, as well as the advent of new drugs, which result in better results associated with the reduction of side effects to patients. To keep up with these advances, hospital environments must be adequate mainly in relation to new technologies and equipment. In hospital units already in operation, these environments need reforms that must follow specific standards to ensure a minimum standard of care for patients, either by the number and type of professionals, as by the physical structure and equipment to assist in the treatment and eventual cure of patients. The objective of this work is to describe the reform process of the Hospital das Clínicas (HC) of Ribeirão Preto - SP and the implementation of the Nuclear Medicine Laboratory and PET-CT, considering the requirements prescribed in RDC N° 50 - Collegiate Board Resolution number 50 and norms of the National Nuclear Energy Commission (CNEN). To achieve this objective, a bibliographic review was carried out in order to guide the theoretical foundation on the theme and, in sequence, the case study in question was approached, contemplating its characterization, the agents involved, planning and logistics, the scope and specificities of the reforms and its comparative description, considering the precepts of RDC N° 50 and pertinent norms. In conclusion, it was verified the compliance with the normative requirements during the process of reform of the hospital environments of the Hospital das Clínicas (HC) of Ribeirão Preto – SP, despite the difficulties and challenges in carrying out these processes in a hospital in full care to patients.
Improvements at the Hospital das Clínicas in Ribeirão Preto – SP: reforms to adapt and implement the Nuclear Medicine and PET - CT Laboratory
Keywords: Hospital das Clínicas; RDC N°50; Ambiente hospitalar; Reforma com adequação; Laboratório de medicina nuclear; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL